RESULTS OF RETROGRADE TRANSURETHRAL HOLMIUM LASER ENUCLEATION OF THE PROSTATE FOR BENIGN PROSTATIC HYPERPLASIA AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of retrograde transurethral enucleation of the benign prostatic hyperplasia using Holmium laser at Vinmec Times City International General Hospital.Materials and methods: A cross-sectional descriptive study was conducted on 64 patients diagnosed with benign prostatic hyperplasia who underwent Holmium laser surgery at Vinmec Times City International General Hospital from February 2022 to June 2025.Results: The mean age of 64 patients was 69.7 ± 9.33 years; average BMI was 22.0 ± 2.04 kg/m²; mean prostate volume was 68.5 ± 41.21 ml; mean prostate-specific antigen was 5.37 ± 4.08 ng/ml. Comorbidities were present in 34.4% of patients; no intraoperative complications were recorded. Mean enucleation time was 70.78 ± 22.01 minutes; morcellation time was 25.39 ± 7.73 minutes; total operative time was 96.17 ± 28.37 minutes. Bladder irrigation duration averaged 41.78 ± 20.08 hours; catheterization time was 62.30 ± 28.11 hours; postoperative hospital stay was 4.08 ± 3.29 days. IPSS decreased from 21.4 ± 3.4 preoperatively to 5.98 ± 2.30 at 1 month, 5.20 ± 1.71 at 3 months, and 4.38 ± 1.64 at 6 months (p < 0.05). Maximum urinary flow rate improved from 4.86 ± 3.78 ml/s pre-op to 16.13 ± 2.92 ml/s at 1 month, 18.72 ± 3.69 ml/s at 3 months, and 20.33 ± 4.11 ml/s at 6 months (p < 0.05). Quality of life scores improved from 4.59 ± 0.68 to 1.98 ± 0.77 at 1 month and 1.75 ± 0.67 at 6 months (p < 0.05). No Clavien-Dindo complications grade ≥ III were observed; 73.4% of patients achieved Qmax > 15 ml/s at 3 months; 89.1% had no urinary incontinence; 67.2% met the Trifecta criteria.Conclusion: Retrograde transurethral Holmium laser enucleation of the prostate is a safe and effective treatment for benign prostatic hyperplasia at Vinmec Times City International General Hospital, significantly improving lower urinary tract symptoms, increasing urinary flow, enhancing quality of life, shortening hospital stay, with low complication rates, and achieving the Trifecta standard.
Keywords: Benign prostatic hyperplasia, HoLEP, Holmium laser, endoscopic surgery, Vinmec Times City.